MASONRY INFILL'S EFFECT FOR PUSHOVER ANALYSIS BEHAVIOUR OF REINFORCED CONCRETE STRUCTURE - JULIANUS A. (NIM 15004024) dan ANDREAS NUGROHO JATI (NIM 15004061), DIEGO
In reinforced concrete structure, Masonry infill panels can be frequently found as non-structural elements. Under construction process, The masonry infill panels is often installed after the main structure, such as beam, coloumn and plate, finish constructed and considered as non-structural effect so their presence is often ignored. In several reinforced concrete structure cases with earthquake loads effect, masonry infill panels give a lot of effects for taking lateral forces. The cracks of masonry infill panels show that lateral loads was transferred from portal to masonry infill panels. The objective of this research is to design masonry infill structure with assuming that masonry infill as equivalent strut model. This type of structure is compared with open frame structure. The factors,which the writers compare with, are about capacity and the ductility of the whole structure. Besides that, the collapsed behaviour of the structure is analyzed to see the probability of soft story collapsed. The collapsed behaviours of reinforced concrete frame with masonry infill due to lateral force from earthquake loads are complicated and non linier. To get the parameters of comparing factors, pushover analyzing was used to analyze the effect of masonry infill panels for reinforced concrete structure with some kinds of configuration of masonry infill panels. The analyzing result shows a capacity curve which is used to get capacity and ductility of the whole structure. Installed of masonry infill panels gives effect to the structure and makes the structure more stiffness than before. The effects of collapsed behaviour between the structure with infill panels and open frame structures give the differences of failure mechanism of the whole structure. It also gives effects of capacity and ductility for the whole structure.